O Psicólogo na assistência estudantil: interfaces entre psicologia, saúde e educação - Oliveira, Aparecida Beatriz de (2016)
The presence of School Psychology in Higher Education has been gradually research object within the Brazilian postgraduate. In this sense, this study investigates the role of psychologists in student assistance in higher education. The objective of the study is to identify and analyze the practices developed by psychologists in student assistance public federal universities in Minas Gerais, using as a theoretical epistemological presuppositions of historical-cultural perspective and School Psychology Review. The research of qualitative approach, with the participation of 19 psychologists who answered the questionnaire, corresponding to 43.18% of the total of 44 professionals located. The content analysis was performed of the information built through this instrument and subsequently elaborated three analytical axes, considering the most significant issues in relation to the purpose of the investigation. The first axis Profile of the psychologists found that training time is 10 years on average, 79% had previous work experience to university in psychology or other areas; most majored in public federal universities of Minas Gerais; all of them have sought to invest in broad sense postgraduate courses and / or strict sense, such as training courses, improvement and / or other forms of continuing education and the male proportion in this blunts up sector in relation to national and mining scenario. In the second axis, which refers to the Performance of psychologists in student assistance, we note that the predominant public on student assistance are college students and work together with the teachers are considered an important challenge to be faced and a space to be conquered. Another challenge mentioned was the existence of references about the role and the psychologist in student assistance, creating difficulties and awakening the desire of professionals to organize themselves to facilitate its construction. As regards the methods of operation, we observe traditional practices, with the predominance of individual care arrangements for the student, which is used by many professionals as a starting point for the development and implementation of programs / projects and group focus modes or collective. In addition to the clinical approach in psychotherapy and group guidance, we see the development of various activities aimed at promoting health, quality of life and integral development of the university, which include interface shares of Psychology with the Health and Education. Most of the psychologists acts as a team made up of professionals connected to the area of human and / or health, and the composition of teams of the structural factors of their identity in student assistance. The third axis, Conceptions about the psychologist's role in student assistance, the School Psychology and Education, we ascertained that the design of the professionals about their role demonstrates the Psychology interface / Health / Education in a health promotion perspective of the college student and psychologist active in student assistance is a school psychologist, although it may not be designated as such. They believe to contribute to education from the service to the student perspective, of their participation in student assistance policies and institutional intervention. We ended pointing out some suggestions for the improvement of the psychologist in student assistance and indicating the limits of this research and some possibilities for future research. We understand the importance of this research lies in the recognition and appreciation of the work done by the school psychologist at student assistance in higher education, as well as the finding that the object of study and performance of School Psychology in this endeavor is the encounter between the subject, the education and Health.